Praktik Pernikahan Dibawah Tangan Oleh Mantan Pejabat KUA Sebagai Wali Hakim Ditinjau dari PMA Nomor 30 Tahun 2005: Studi Kasus di Desa Tanjung Anom - Lidiyanti, Nisa; Hasanah, Uswatun (Kamaya: Jurnal Ilmu Agama, 2025)
This research discusses the practice of underhanded marriages by former KUA officials as guardian judges which occurred in Tanjung Anom village. Marriage under the hand is legally valid if all the pillars and conditions of marriage are fulfilled. However, the law changes to become haram if it causes harm. This research aims to determine the status of marriages carried out by several couples with former KUA officials who act as guardian judges when the guardian of nasab is not present in the marriage and the legal impact of marriages under the hands of former KUA officials as guardian judges. The research method in this research uses empirical legal research or what is usually called field research. The data sources used are primary and secondary data sources. The primary data source is interviews with the public and former KUA officials. Secondary data sources consist of data obtained from books and journals related to the problem. The results of the research concluded: the status of a private marriage by a former KUA official as a judge’s guardian is false or invalid because in a private marriage there is no judge’s guardian and the judge’s guardian only applies to marriages that are legal according to the state. According to Minister of Religion Regulation Number 30 of 2005, the guardian judge is the Head of the District Religious Affairs Office who is appointed by the Minister of Religion to act as marriage guardian for prospective brides who do not have guardians. A marriage solemnized in the presence of an unauthorized marriage registrar or an unauthorized marriage guardian may be requested to be annulled. The solution to an invalid underhanded marriage is Remarriage (Tajdid Nikah).